MENINGKATKAN KETERAMPILAN SOSIAL DENGAN MENGGUNAKAN MODEL PEMBELAJARAN DISCOVERY LEARNING PADA MATA PELAJARAN IPAS MATERI INDONESIAKU KAYA BUDAYA UNTUK PESERTA DIDIK KELAS IV SDN 80/1 MUARA BULIAN - Revina Voseka Revina; Muhammad Sofwan; Khoirunnisa (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This research aims to describe the implementation of the Discovery Learning learning model in improving social skills for class IV students in the science and science subject My Indonesia Rich Culture Material at SDN 80/1 Muara Bulian. Based on the results of initial research observations, it was found that at SDN 80/1 Muara Bulian in Class IV, the social skills possessed by students were still low. It was seen that there was a lack of collaboration or cooperation between students and there were still many students who used rude language towards their friends. Class Action Research (PTK) consists of 2 cycles with each cycle having 2 meetings where data is taken from the teacher's implementation observation sheet in implementing the Discovery Learning learning model and the student's social skills observation sheet. This research was carried out in 4 stages, namely planning, implementation, observation and reflection. The research results show that the application of the Discovery Learning model in science learning has resulted in a significant increase in students' social skills. Initially, social skills were at the level of 56.42% in the first cycle, but increased to 76.22% in the second cycle. Thus, it can be concluded that the implementation of the Discovery Learning model in science and science learning has succeeded in improving the social skills of class IV elementary school students.